Literature Review Terhadap Peran Buku Teks Bahasa Arab di Madrasah Ibtidaiyah - Utami, Fajar; Kesuma, Guntur Cahaya; Syahril, Sulthan; Ghazi, Fachrul (JILSA (Jurnal Ilmu Linguistik dan Sastra Arab), 2024)
Arabic textbooks play a very important role in Madrasah Ibtidaiyah (Islamic primary schools) in language acquisition and understanding the religious and cultural aspects of Arabic. This research examines the role of Arabic textbooks in the learning process, teaching practices, and curriculum implementation in Madrasah Ibtidaiyah. Using a qualitative approach, this study analyzes various themes, such as textbook content, conformity to the curriculum, and student engagement. The results show that Arabic textbooks support the development of students' basic language skills, but lack interactive exercises and variations in assessment. To maximize their effectiveness, textbooks should be combined with innovative teaching strategies and continuously adapted to evolving educational needs. A well-designed textbook, together with diverse teaching methods, can improve student learning outcomes. Future research is recommended to focus on developing textbooks with modern pedagogical approaches that involve feedback from teachers and students, in order to increase relevance and engagement. Overall, Arabic textbooks have a vital role to play in Madrasah Ibtidaiyah, but their impact can be optimized through continuous improvement of teaching design and practice.